Education for cooperation and active citizenship through an experience of school-work alternation: An example from the province of Trento - Piccoli, Alessandra; Michelotti, Riccarda (Formazione & insegnamento, 2023)
What is the social value of alternating between school and work? Can a school-work alternation project promote the values of the cooperative movement? This article aims to partially address these questions by examining a project conducted in the province of Trento. The training program involved introducing participants to cooperation and video production. Subsequently, the project encouraged the creation of video interviews with elderly co-operators, followed by the editing of approximately ten videos by young participants. At the conclusion of the project, three teachers and twelve students were interviewed to explore their perception of the alternation experience, the shift in perspective regarding the cooperative movement, the values they identified through the experience, and its impact on their active engagement in society. The findings indicate that school-work alternation is not only an effective means of imparting specific and cross-disciplinary skills but also of promoting increased civic activism.